Cyber-ostracism and its relation to depression among Chinese adolescents: The moderating role of optimism. (1st March 2018) - Niu, Geng-Feng; Zhou, Zong-Kui; Sun, Xiao-jun; Yu, Feng; Xie, Xiao-Chun; Liu, Qing-Qi; Lian, Shuai-Lei
Abstract: Internet has been a popular medium and means to interconnect with others, with increasing opportunities for inclusion; at the same time, being ignored and excluded, a phenomenon referring to cyber-ostraism also increased. This study investigated the influence of cyber-ostracism on Chinese adolescents' depression, and the moderating role of optimism between them. First, a scale with 14-item was developed to measure the cyber-ostracism experience of adolescents. Then, a survey was conducted among 1626 Chinese adolescents aged 12–18, and the results showed that: (1) cyber-ostracism was positively correlated with depression, while optimism was negatively correlated with depression, (2) optimism could moderate the influence of cyber-ostracism on depression, with a stronger association for adolescents with low level of optimism. Results indicated that cyber-ostracism is a negative interpersonal experience as ostracism in real life, while optimism could alleviate the detrimental effect of cyber-ostracism. Highlights: A cyber-ostracism experience scale for adolescents was developed. Cyber-ostracism would increase the risk of depression. Cyber-ostracism is a painful and distressful experience as ostracism in real life. Optimism optimisim could alleviate the detrimental effect of cyber-ostracism.